On energy management, load balancing and replication - Lang, Willis; Patel, Jignesh M.; Naughton, Jeffrey F. (International Conference on Management of Data, 2010)
In this paper we investigate some opportunities and challenges that arise in energy-aware computing in a cluster of servers running data-intensive workloads. We leverage the insight that servers in a cluster are often underutilized, which makes it attractive to consider powering down some servers and redistributing their load to others. Of course, powering down servers naively will render data stored only on powered down servers inaccessible. While data replication can be exploited to power down servers without losing access to data, unfortunately, care must be taken in the design of the replication and server power down schemes to avoid creating load imbalances on the remaining "live" servers. Accordingly, in this paper we study the interaction between energy management, load balancing, and replication strategies for data-intensive cluster computing. In particular, we show that Chained Declustering – a replication strategy proposed more than 20 years ago – can support very flexible energy management schemes.